Community Education on Hypertension in Batua Dua Village's Simalungun Regency Area - Arsiaty Sumule; okta, isma; Maswan Daulay; Salim Efendy; Fendy Prasetyawan; Ratna Mildawati (Amaluna: Jurnal Pengabdian Masyarakat, 2024)
According to the 2018 Indonesian Basic Health Research Statistics (Riskesdas), 34.11% of Indonesians aged 18 or older have hypertension, with 8.36% of those affected based on diagnosis. According to the American Heart Association, the number of individuals with hypertension rises annually, and the average death rate from the condition increased by almost 21% between 2000 and 2010. Additionally, the death rate significantly increases in at least 46% of individuals with hypertension. The purpose of this service is to educate clients both before and after counseling on lifestyle compliance. The strategy is to distribute information on hypertension, which can raise public awareness by demonstrating positive answers and accuracy in responding to the questions. There was a difference in knowledge between the 20 respondents who participated in the counseling before and after it was provided.